Genetic influences on puppy and juvenile guide dog behaviour - Hunt, Rebecca (2025)
The influence of genetics on behaviour in dogs has been under constant debate and is of particular importance to assistance dog organisations, where breeding suitable dogs for the working role is important to maximise resources and efficiencies and improve dog welfare. The aims of this thesis were to determine the genetic influences on guide dog behaviour through pedigree and genome-based heritability estimates for data captured through questionnaires and a behavioural observation assessment. Behavioural questionnaires were collected in a cohort of juvenile guide dog puppies at five months (5M, n=551), eight months (8M, n=2317) and 12 months (12M, n=1537) of age using a previously validated questionnaire, the refined-Puppy Walker Questionnaire (r-PWQ). Due to a difference in component (group of questions) structure for this population, the questionnaire was adjusted. A pedigree-based heritability analysis was undertaken, with the 5M Anxiety component indicating the highest heritability (h2=0.29). Heritabilities at 8M and 12M were below 0.1 for all behavioural components. Using the same data, a genomic-based heritability analysis was undertaken for 96 dogs at 8M and 12M. Genomic-based heritabilities were higher than pedigree-based estimates and following a genome wide association study (GWAS), Excitement behaviours at 12M and Separation behaviours at 8M indicated single nucleotide polymorphisms (SNPs) approaching significance. Links were found between these behaviours in dogs and genes associated with obsessive/depressive disorders in humans (attention deficit hyperactivity disorder, alcoholism, depression and schizophrenia).